Extremity soft tissue sarcoma in the elderly: Are we overtreating or undertreating this potentially vulnerable patient population?. Issue 8 (12th April 2019) - Gingrich, Alicia A.; Bateni, Sarah B.; Monjazeb, Arta M.; Thorpe, Steven W.; Kirane, Amanda R.; Bold, Richard J.; Canter, Robert J.
Abstract: Background: As the U.S. population ages, differences in oncologic outcomes among the elderly have been recognized. Our objective was to analyze the clinical, pathologic, and treatment outcomes for elderly soft tissue sarcoma (STS) patients, hypothesizing significant differences in the management and response to therapy. Methods: Using the National Cancer Database, we identified 33 859 patients with nonmetastatic extremity STS. We defined elderly as ≥74 years in age and compared patient and treatment variables between adult and elderly patients. Cox‐proportional hazards analysis was used to determine predictors of overall survival (OS). Results: We identified 8504 elderly patients. Significant differences in histologic subtype, grade, and facility type between elderly and nonelderly patients ( P < 0.05) exist. Elderly patients were less likely to undergo R0 resection ( P = 0.001) and had a higher 90‐day mortality ( P = 0.001). Surgical elderly patients experienced superior OS compared with nonsurgical patients ( P = 0.001). Among elderly patients, younger age, and female sex, lower Charlson‐Deyo score, lower grade, smaller tumors, surgical resection, negative surgical margins, and radiation therapy were associated with better OS. Conclusions: Key differences exist in elderly extremity STS patients, including a narrower benefit/risk ratio with surgical management. These data highlight that elderly patients represent a distinct cohort for whom more careful selection appears indicated.